Porous single-crystalline titanium dioxide at 2 cm scale delivering enhanced photoelectrochemical performance - Fangyuan Cheng (Nature Portfolio, 2019)
Porous single crystals in large size can significantly enhance their functionality owing to the structural coherence and large surface area. Here the authors show porous single-crystalline titanium dioxide based photoelectrodes with large dimensions leading to improved photoelectrochemical performance.